HOW 'NATIVES' WORK: POLITICAL JUDGEMENT AND COHESION THROUGH RITUAL INTERACTION AMONG MINISTERS. (2nd September 2015) - 6, PERRI
Abstract : How do political administrations sustain whatever kinds of cohesion they do, over their time in office? Although recent research emphasizes institutions, sometimes institutions also weaken cohesion. Informal institutions are more important than formal ones in shaping styles of political judgement in governing administrations. But how can institutional processes explain both weakening and strengthening? This article develops a neo‐Durkheimian theory. It proposes that informal institutions should be understood as operating through very particular kinds of practices, which are enacted in a limited number of basic kinds of ritual interaction order. The article innovates by showing how written ritual in government interacts with face‐to‐face ritual in cultivating styles both of thought and of emotions to sustain positive and negative feedback dynamics. The argument is illustrated by analysing negative rites of blame and accusation and positive rites of self‐assertion during positive feedback in the individualistic interaction order in Harold Wilson's 1960s Cabinet.